Functional task kinematic like biomarkers with RGB-D camera in axial spondyloarthritis and non-specific low back pain - Trinidad-Fernández, Manuel (UMA Editorial, 2022)
Introduction: Axial spondyloarthritis (AS) and non-specific low back pain (NSLBP) affect the back causing movement limitations. RGB-D cameras can develop a virtual skeleton model from which to extract kinematic information about movement. Objective: The objective was to analyze the use of the RGB-D camera as an assessment tool in patients with AS and subacute and chronic NSLBP. Two validation studies of the camera were carried out in these clinical populations and two studies were subsequently carried out to test its applicability. Results: CLINIMETRIC CHARACTERISTICS OF RGB-D CAMERA IN AXIAL SPONDYLOARTHRITIS: Bending task have obtained good results in validity and reliability using an RGB-D camera. It is necessary to further investigate the Chair task in linear acceleration. REFERENCE VALUES OF CLUSTERING RGB-D CAMERA OBTAINED ACCORDING TO DISEASE SEVERITY OF AXIAL SPONDYLOARTHRITIS: A PILOT STUDY: These results provide more preliminary insight into the movement analysis in AS with an RGB-D camera comparing to different severity groups: Group with high disease impact and group with low disease impact. CLINIMETRIC CHARACTERISTICS OF RGB-D CAMERA IN NON-SPECIFIC LOW BACK PAIN: Kinematics analysed during the Sit-to-stand test, bending test, and sock test reached validity, reliability, and responsiveness measures from moderate to good. CLUSTERING RGB-D CAMERA OBTAINED KINEMATIC OUTCOMES ACCORDING TO DISEASE SEVERITY OF NON-SPECIFIC LOW BACK PAIN: There were differences between NSLBP subjects and non-LBP subjects: velocity and accelerations in Bending test, accelerations in STS test and acceleration in Sock test. The linear acceleration during the Bending test and STS test were significantly different between severity subgroup.
Conclusions: The RGB-D camera can be a valid evaluation tool in patients with AS and subacute and chronic NSLBP, depending on the functional test. Furthermore, the specific kinematic variables collected by an RGB-D camera can show kinematic results and distinguish different severities when evaluating these patients.
Keywords: Fisioterapia - Tesis doctorales; Spondyloarthritis; Low back pain; Motion capture; Functional test; Camera